2021
DOI: 10.3390/gels7040236
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Cellulose-Co-AMPS Hydrogel for Personal Hygiene Applications Using Cellulose Extracted from Corncobs

Abstract: Cellulose-based hydrogels were prepared by the extraction of cellulose from corncobs after the removal of lignin and hemicellulose with the use of alkali–acid treatment. Acrylate-based hydrogels presently available for personal hygiene uses are not biodegradable. In this study, a biodegradable cellulose-co-AMPS personal hygiene hydrogel was synthesized. The hydrogel was synthesized by graft co-polymerization of 2-acrylamido2-methyl propane sulfonic acid onto corncob cellulose by using potassium persulfate (KPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…In line with previous research, Enawgaw et al [ 29 ] synthesized a corncob cellulose-co-AMPS (2-acrylamide-2-methylpropane sulfonic acid)-based hydrogel by using a crosslinking agent in the form of borax decahydrate and potassium persulfate (KPS) as an initiator. It was found that the manufactured hydrogel had a swelling ratio to urine solution lower than that of hydrogel to water.…”
Section: Types Of Hydrogelsmentioning
confidence: 61%
See 1 more Smart Citation
“…In line with previous research, Enawgaw et al [ 29 ] synthesized a corncob cellulose-co-AMPS (2-acrylamide-2-methylpropane sulfonic acid)-based hydrogel by using a crosslinking agent in the form of borax decahydrate and potassium persulfate (KPS) as an initiator. It was found that the manufactured hydrogel had a swelling ratio to urine solution lower than that of hydrogel to water.…”
Section: Types Of Hydrogelsmentioning
confidence: 61%
“…In terms of ability, cellulose has a stronger structure, higher degree of crystallinity [ 27 ], and very high swelling ratio [ 29 , 30 ] than other polysaccharide polymers such as starch and glycogen for hydrogel materials. This is because starch and glycogen are connected to α-1.4 or α-1.6 glycosidic chains, while cellulose is connected to β-1.4 glycosidic chains, which means that it will form a structure in the form of fibers and be more resistant to degradation because the position of monomer residues in cellulose is reversed (trans configuration) and bonded well with an increasing number of chain bonds.…”
Section: Types Of Hydrogelsmentioning
confidence: 99%
“…Since their design, the properties of hydrogels can be tuned to mimic the mechanical, biochemical, and functional characteristics of the soft tissues. The biomimetic materials are applied for controlled drug delivery [4,6,41,58,59,108,122,126,127,178,179], in regenerative medicine (tissue engineering, modulating tissue environment to promote the tissue repair) [3,4,176,180], biosensors and actuators [4,9,[11][12][13]86,176,[180][181][182], bioprinting [4,[10][11][12], 3D cell culture [4,42,46,79,177], imaging for medical diagnostics and therapy [183][184][185], personal healthcare and hygienic products [16,165], etc. A variety of hydrogels responsive to different external stimuli were reported: temperature [4,9,22,35,53,78,…”
Section: Stimuli-responsivenessmentioning
confidence: 99%
“…From a chemical point of view, the hydrogels can be obtained from natural or synthetic water soluble (co)polymers of various structures and architectures, interpenetrated polymer networks (IPNs), proteins, peptides, clays, multicomponent systems, etc., having different morphologies and functions [1][2][3]. In particular, smart networks able to respond to physical, chemical, and biological stimuli gained much attention for a wide range of applications: tissue engineering [4], bone regeneration [5], controlled-release drug delivery vehicles [6], wound healing [7], soft robotics [8], biosensing [9], intelligent electronics and artificial intelligence [10], actuators [11][12][13], stretched electronic devices [14], hygiene products [15,16], contact lens [17], cosmetics [18], food nutrition and health, food safety and food engineering and processing [19], advanced wastewater treatment [20], catalysis [21][22][23], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose ethers are one of the main cellulose derivatives that are produced by substitution of hydroxyl groups to methyl, hydroxyethyl or hydroxypropylmethyl functional groups within the macromolecular backbone. [1][2][3] It has been demonstrated in previous studies that these changes can decrease the crystallinity of cellulose, whereas the water solubility and gelation properties can be improved. 4,5 Among the cellulose ethers, HPMC has been a well-known biopolymer with application in different industries including constructions, ceramics, plastics, foods, textiles and pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%